Extracellular Citrate Is a Trojan Horse for Cancer Cells - Petillo, Agata; Abruzzese, Vittorio; Koshal, Prashant; Ostuni, Angela; Bisaccia, Faustino (Frontiers in Molecular Biosciences, 2020)
The first intermediate in the mitochondrial tricarboxylic acid (TCA) cycle is citrate, which is essential and acts as a metabolic regulator for glycolysis, TCA cycle, gluconeogenesis, and fatty acids synthesis. Within the cytosol, citrate is cleaved by ATP citrate lyase (ACLY) into oxaloacetate (OAA) and acetyl-CoA; OAA can be used for neoglucogenesis or in the TCA cycle, acetyl-CoA is the precursor of some biosynthetic processes including the synthesis of fatty acids. Accumulating evidence suggest that citrate is involved in numerous physiological and pathophysiological processes such as inflammation, insulin secretion, neurological disorders and cancer. Considering the crucial role of citrate to supply the acetyl-CoA pool for fatty acid synthesis and histone acetylation in tumors, in this study we evaluated the effect of citrate added to the growth medium on lipid deposition and histone H4 acetylation in hepatoma cells (HepG2). At low concentration, citrate increased both histone H4 acetylation and lipids deposition; at high concentration, citrate inhibited both, thus suggesting a crucial role of acetyl-CoA availability, which prompted us to investigate the effect of citrate on ACLY. In HepG2 cells, the expression of ACLY is correlated with histone acetylation, which in turn depends on the citrate concentration. A decrease in H4 acetylation was also observed when citrate was added at high concentration to immortalized human hepatic cells (IHH), whereas ACLY expression was unaffected indicating a lack of control by the histone acetylation. Considering the strong demand for acetyl-CoA but not for OAA in tumor cells, the exogenous citrate would behave like a trojan horse that carries OAA inside the cells and reduces ACLY expression and cellular metabolism. In addition, this study confirmed the already reported dual role of citrate both as a promoter of cell proliferation (at lower concentrations) and anticancer agent (at higher concentrations) providing useful tips on the use of citrate for the treatment of tumors.